Microglia and synapse interactions: fine tuning neural circuits and candidate molecules - Miyamoto, Akiko; Wake, Hiroaki; Moorhouse, Andrew J.; Nabekura, Junichi (Frontiers in Cellular Neuroscience, 2013)
Brain function depends critically on the interactions among the underlying components that comprise neural circuits. This includes coordinated activity in pre-synaptic and postsynaptic neuronal elements, but also in the non-neuronal elements such as glial cells. Microglia are glial cells in the central nervous system (CNS) that have well-known roles in neuronal immune function, responding to infections and brain injury and influencing the progress of neurodegenerative disorders. However, microglia are also surveyors of the healthy brain, continuously extending and retracting their processes and making contacts with pre- and postsynaptic elements of neural circuits, a process that clearly consumes considerable energy. Pruning of synapses during development and in response to injury has also been documented, and we propose that this extensive surveillance of the brain parenchyma in adult healthy brain results in similar “fine-tuning” of neural circuits. A reasonable extension is that a dysfunction of such a homeostatic role of microglia could be a primary cause of neuronal disease. Indeed, neuronal functions including cognition, personality, and information processing are affected by immune status. In this review we focus on the interactions between microglia and synapses, the possible cellular and molecular mechanisms that mediate such contacts, and the possible implications these interactions may have in the fine tuning of neural circuits that is so important for physiological brain function.